Pengaruh Komik Digital Di Instagram Sebagai Media Kampanye Politik - ARIN RISKI ASTARIA; Fitriyah - - (Journal of Politic and Government Studies, 2020)
The 2019 presidential election was enlivened by old faces, namely Joko Widodo and Prabowo. The striking difference is that during this period, there was a new "commodity" of voter candidates, namely the millennial group whose age range is between 17 to 34 years. The unique characteristics of this group is that they demanded each campaign team to create new innovations in campaigning so that they can win the votes of millennial voters. One of the interesting innovations of this campaign that caught the researcher’s eyes is the use of digital comics as a campaign medium on Instagram by the Jokowi-Amin campaign team. More specifically, the researcher wants to examine the effect of digital comics as a campaign medium on the political orientation of millennial voters by covering cognitive, affective, and evaluatif orientations aspects. The researcher used a quantitative research method with data collection techniques using a questionnaire instrument that was distributed to 100 respondents with predetermined kriteria. In addition, the analytical techniques used by researchers are the Product Moment Test and Simple Linear Regression Test with the discussion using Almond's theory of political orientation and Lasswell's theory of political communication. The result of this research is that digital comics as a campaign medium have a goof quality and also have an influence on the political orientation of millennial voters with the most increasing aspect of political orientation is the evaluatif orientation in the form of judgments, the second most influenced aspect is cognitive orientation in the form of knowledge and the least affected aspect is affective orientation. In addition, the orientation is positive with a strong and reliable correlation between the two variabels. The effect of comic as a medium campaing on millennial’s political orientation is 59,3% and if quality of comic is added 1%, the political orientation’s value will increase as many as 1,753. The researcher hope that in the next research, it can be studied with larger scale with more respondents so it can represent the whole population and also carry out their political behavior so that the result of the research are clearer and more focused.